Short interest and stock returns: evidence from the UK (Gregynog 2011). - Mohamad, Azhar (2011)
This paper examines the information content of short interest by examining whether firms that experience significant increase in short interest subsequently experience negative returns. Using the UK daily short interest data from the period of September 2003 to April 2010, we find a significant negative relation between increases in short interest and subsequent returns on equal-weighted basis. The results indicate informational content of increases in short interest which is consistent with Diamond and Verrecchia (1987) hypotheses.